STUDI EKSPERIMEN PENGGUNAAN BETON BERAGREGAT DAUR ULANG TERHADAP SERANGAN NATRIUM SULFAT DENGAN SIKLUS KERING-BASAH - Rivo Arrohman Fauzi; Devi Nuralinah; Eva Arifi (Jurnal Mahasiswa Jurusan Teknik Sipil, 2023)
Infrastructure development in Indonesia is currently growing rapidly in coastal areas because Indonesia has the second longest coastline in the world, development in coastal areas has a high risk of damage due to sodium sulfate contained in seawater. The ebb and flow of seawater cause parts of the concrete to be submerged during high tide and exposed to air during low tide. Sodium sulfate attack with dry-wet cycle 3:1 is known to be the most damaging to concrete. The use of recycled coarse aggregate is also expected to be a solution to the increasing amount of concrete waste from construction. This study used cylindrical specimens measuring 15 x 30 cm using normal coarse aggregate (NCA) and recycled coarse aggregate (RCA). The dry-wet cycle begins when the concrete is 28 days old with 3 dry days and 1 wet day using 4% Na2SO4 by weight of water. The tests were carried out at the age of the concrete at 28, 84, and 168 days. From this study, it is known that the value of compressive strength of concrete is directly proportional to the value of the modulus of elasticity of concrete, where the value of the compressive strength and modulus of elasticity in RCA concrete is lower than that of NCA concrete. In addition, there is a decrease in mass in both variations with the largest decrease in RCA concrete. Keyword: Sodium sulfate, Wet-dry ratio, Recycled Coarse Aggregate (RCA)